The Data Drill: An Opportunity for Researchers to Practice Accessing and Interpreting Data - Sandi Caldrone; Yali Feng (Journal of eScience Librarianship, 2025)
It is difficult to engage researchers in workshops on data management best practices when there are so many other demands on their time and attention. Even when interest is high, attendance is often low. In response to this challenge, the Research Data Service and the School of Social Work at the University of Illinois Urbana-Champaign partnered to develop a new data management learning activity, the data drill. Like a fire drill, the data drill is a safe way to practice a stressful scenario, in this case, accessing and interpreting a dataset. In this paper, we describe how we designed the data drill, discuss the results of three pilot drills we conducted, and outline our plans to improve and expand upon this activity based on our experiences. Each data drill participant selected a dataset they deemed important to their research but that they were not currently using, and attempted to locate, access, and interpret the data during a virtual meeting with one to two librarian facilitators who helped troubleshoot issues as they arose. This allowed participants to stress-test how well their data is organized and documented and provided facilitators with a window into the researcher-data relationship and a unique opportunity to provide highly individualized support with immediate and long-term benefits.